Omission of alcohol skin cleansing and risk of adverse events in long-term care residents undergoing COVID-19 vaccination: A cohort study - Benoit Lafleur; Jollee Fung; Chris P. Verschoor; Sacha Dubois; Noni E MacDonald; Anna Taddio (Taylor & Francis Group, 2024)
Despite a lack of clinical data demonstrating the effectiveness of alcohol swab cleansing prior to vaccinations as a prophylactic measure to prevent skin infections, it is recommended for vaccine administration by the Canadian Immunization Guide. The objective of this study was to evaluate the risk of adverse events after omitting alcohol skin cleansing in long-term care (LTC) residents receiving vaccinations during the COVID-19 pandemic. Two medium-sized LTC homes participated in a cohort study, whereby one LTC used alcohol swab cleansing prior to resident vaccinations and the other did not. All residents received two doses of the BNT162b2 COVID-19 vaccine separated by an average (SD) 29.3 (8.5) days. The electronic chart records of participants were reviewed by researchers blinded to group allocation to assess for the presence of adverse events following immunization (AEFI), including reactogenicity, cellulitis, abscess, or systemic reactions. Log-binomial regression was used to compute risk ratios (with 95% confidence intervals) of an AEFI according to alcohol swab status. 189 residents were included, with a total of 56 AEFI between the two doses. The risk of reactogenicity (adjusted RR 0.54, 95% CI 0.17-1.73) or systemic reactions (adjusted RR 0.75, 95% CI 0.26-2.13) did not differ for the residents that received alcohol skin antisepsis compared to those that did not. There were no cases of cellulitis or abscess. This study did not demonstrate an elevated risk of AEFI in LTC residents receiving two doses of the BNT162b2 mRNA COVID vaccine without alcohol skin antisepsis.